Characterization and thermostability study of invertase by Aspergillus niger in submerged culture - Nurul Izzah, Ahmad (2013)
Invertase is a commercially important enzyme used for hydrolysis of sucrose.The hydrolysis of sucrose yields a mixture of glucose and fructose, or famous as name invert syrup, this enzyme was widely used in food and beverage industries.Objectives of this research are to study the pH and thermostability of invertase by Aspergillus niger,to study the enzyme kinetics of invertase and to study the effect of sucrose concentration during incubation towards invertase activity.A.niger produced high levels of invertase under culture conditions (potato dextrose agar) on fourth day of incubation at an optimum temperature 30OC,inoculum at 30OC at 250 rpm and using sucrose as a substrate by submerged fermentation(SmF)also with same culture conditions.Separation between enzyme and other cell was done by centrifugation and continued with study the pH and thermostability of enzyme by terminated by heating. Thermostability of enzyme were investigated by determining the enzymatic reaction subjected to 40OC, 45OC, 50OC, 55OC and 60OC.Michaelis-Menten parameters (Vmax and Km) were determined for four different sucrose concentration which are 0.2, 0.4, 0.6, 0.8 g/L. Result suggested that optimum pH is 5.0 and temperature is 55OC.While both Vmax and Km would increase at higher temperatures because temperature will alter the shape of enzyme by changing its ionic form at active site.